Nutrient dynamics in the Bohai and North Yellow seas from seasonal to decadal scales: Unveiling Bohai Sea eutrophication mitigation in the 2010s - Zheng, Li-wen; Zhai, Wei-dong (The Science of the total environment, 2023)
The eutrophication status in the central Bohai Sea tends to be mitigated in recent years. To explore the recent nutrient status, seasonal surveys were carried out from 2018 to 2021, covering both the Bohai Sea and the adjacent North Yellow Sea. In recent cold seasons, both dissolved inorganic nitrogen concentration (DIN) and the ratio of DIN to soluble reactive phosphorus were lower than those in 2016. In warm seasons, the variations in nutrients and apparent oxygen utilization were correlated with each other, roughly following the traditional Redfield ratio of N:P:O2 of approximately 16:1:(−138). When historical data for N*, which is the excess DIN related to soluble reactive phosphorus, was collated, the Bohai Sea showed a decreasing trend for N* at a rate of −0.64 ± 0.12 μmol N* kg−1 a−1 between 2011 and 2021. During the same period, the North Yellow Sea N* concentrations (i.e., the oceanic end-member of the Bohai Sea N* dynamics) and the local atmospheric nitrogen (N) deposition (atmospheric end-member) were estimated to decline at rates of −0.22 ± 0.04 μmol N* kg−1 a−1 and − 0.93 ± 0.34 kg N ha−1 a−2, respectively. Consequently, the oceanic and atmospheric changes accounted for 25.7 % ± 28.4 % and 69.0 % ± 42.6 %, respectively, of the Bohai Sea eutrophication mitigation in 2011–2021. On the long-term changes of the Bohai Sea eutrophication, the terrestrial nutrient source has only minor (likely <10 %) impacts, although it certainly affects the spatial distribution of nutrients. This study has implied that coastal eutrophication is a dynamic process that is subject to sea–land–air interactions, and its mitigation needs both local pollution controls and regional environment management. The latter contains the understanding of oceanic changes and external effects of the air pollution control. [Display omitted] •Eutrophication has been mitigated in the Bohai Sea in the 2010s.•Reductions in atmospheric and oceanic nitrogen explain this change.•Terrestrial nutrients mainly affect nearshore nutrient dynamics in the Bohai Sea.